Reconstructing media frames in multimodal discourse: The John/Ivan Demjanjuk trial. (June 2016) - Pentzold, Christian; Sommer, Vivien; Meier, Stefan; Fraas, Claudia
Abstract: This article explores a way to reconstruct the verbally and visually constituted frames used in the coverage of the trial of John/Ivan Demjanjuk, a Ukraine-born U.S. citizen accused of holocaustrelated war crimes. The study looks at an exemplary case of current multimodal discourse, in which written messages and images from broadcasts and press, as well as the comments and visuals that spread through social media, can be seen to relate to each other in framing public issues. To establish a viable perspective that takes into account both the communicative organisation and the semiotic constitution of such discourses, this analysis combines approaches from frame semantics and social semiotics together with recursive sampling and coding. The article then explains the analytical procedures used to reconstruct the framing of the accused as either a responsible culprit or a victim of circumstances. Highlights: Multimodal discourse presents opportunities and challenges for sampling material. We combine qualitative analytical procedures to account for communicative organisation and semiotic composition. We combine methods from frame semantics, social semiotics and qualitative social enquiry to reconstruct media frames. We explore the discourse on the third trial of the alleged Nazi collaborator, John/Ivan Demjanjuk. Demjanjuk is either framed as a responsible culprit or as a victim of circumstances.